Identification of the hand-arm system mechanical impedance by simultaneous measurement of grip, transmitted force and acceleration with an adaptable instrumented handle. Issue 1 (1st January 2017) - Forte, Paola
Abstract: In this paper the results of static and dynamic tests carried out with an instrumented handle are presented and discussed. The instrumented handle was designed and constructed to be directly mounted on the handlebar of a two-wheeled vehicle and it can measure simultaneously grip, force transmitted by the handlebar to the hand and acceleration at the handle interface. The results of repeatability tests on the hand-arm weight and grip static measurement without and with real-time measure feedback show the importance of the use of an instrumented handle to ensure repeatability and also to estimate the influence of such parameters on the dynamic response. On the basis of preliminary dynamic tests conducted with the handle mounted on a shaker, the hand-arm system was characterized on two subjects, through a spectrum of its mechanical impedance as function of the excitation frequency, for different postures and grip levels. The results were compared to literature ideal impedance curves with acceptable agreement. The effect of grip showed to increase impedance in some specific frequency ranges.